Protection against Streptococcus pneumoniae Elicited by Immunization with Pneumolysin and CbpA - Ogunniyi, Abiodun David (American Society for Microbiology, 2001)
The need for the development of cheap and effective vaccines against pneumococcal disease has necessitated the evaluation of common virulence-associated proteins of Streptococcus pneumoniae as potential vaccine antigens. In this study, we examined the capacity of active immunization with a genetic toxoid derivative of pneumolysin (PdB) and/or a fragment of choline binding protein A (CbpA; also known as PspC, Hic, and SpsA) to protect mice from intraperitoneal challenge with medium to very high doses of a highly virulent capsular type 2 pneumococcal strain, D39. The median survival times for mice immunized with the individual protein antigens in different adjuvant combinations were significantly longer than those for mice that received the respective adjuvants alone. Mice immunized with CbpA alone were significantly better protected than mice immunized with PdB alone. Correspondingly, the median survival times for mice that were immunized with a combination of PdB and CbpA were significantly longer than those for mice that received PdB alone but not significantly different from those that received CbpA alone. Mice immunized with the protein antigens in a mixture of monophospholipid A (MPL) and aluminium phosphate (AlPO(4)) adjuvants had higher antibody titers than mice that received the antigens in AlPO(4) alone. Mice immunized with PdB in MPL plus AlPO(4) were also significantly better protected than mice that received PdB in AlPO(4) alone.